KONSEP HAK DAN KEWAJIBAN SUAMI ISTRI DALAM KITAB 'UQUD AL-LUJJAYN DAN RELEVANSINYA DENGAN KONSELING KELUARGA BERBASIS GENDER - KHAFIT PRASETIYO; AHMAD FARUQ (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Rights are the truth and authority to carry out something. Meanwhile, an obligation is something that is done with a sense of responsibility. Rights and obligations are two things that of course go together in the family. For example, in the context of family life, both things must be fulfilled equally. Regarding the rights and obligations of husband and wife in the family is something that is very important to know. These two things are to create peace in the family, especially in matters of gender equality in the household. Equality in the family will create a sakinah, mawaddah, warahmah family. This research is included in qualitative research with a library approach and uses descriptive analytical methods, extrapolation and heuristics. The author uses research in the form of data collection through written sources, both books and journals, related to the concept of rights and obligations according to Sheikh Imam Nawawi al-Bantani in the book 'Uqud al-Lujjayn and related to family counseling according to gender. known as gender aware counseling. According to one of the Salaf scholars who has made great contributions to Islamic scholarship, namely Sheikh Imam Nawawi al-Bantani. Imam Nawawi al-Bantani also published many famous works, one of his works is the book Uqud al-lujjayn fii bayani huququz zawjayni. The concept of rights and obligations of domestic partners explained by Imam Nawawi al-Bantani states that the relationship between husband and wife must have a good social balance. For example, a couple must have a good relationship. In order to build a harmonious household. that the concept of rights and obligations of domestic partners in Uqud al-Lujjayn emphasizes the importance of both parties obeying each other and respecting each other's rights and obligations equally. Sheikh Nawawi al-Bantani also emphasized that in Islam the position of men and women in the eyes of Allah is the same, the only difference is their piety. Gender-based family counseling aims to help individuals overcome family problems related to gender inequality, such as domestic violence and women's dual roles. This approach promotes family healing or provides curative therapy to improve family dynamics. Both approaches, both the Uqud al-Lujjayn concept and gender-based family counseling, prioritize balance, respect and protection of the rights and obligations of husband and wife in accordance with Islamic values ​​and gender justice